Giant low-field magnetocaloric effect in a textured Ni45.3Co5.1Mn36.1In13.5 alloy. (1st July 2018) - Li, Zhenzhuang; Li, Zongbin; Yang, Bo; Zhao, Xiang; Zuo, Liang
Abstract: We demonstrate a remarkable magnetocaloric effect in a directionally solidified Ni45.3 Co5.1 Mn36.1 In13.5 alloy with coarse-grained microstructure and strong 〈001〉A texture. Due to this optimized microstructure and the strong magnetostructural coupling, a giant Δ T ad up to −5.1 K is achieved under low field change of 1.5 T, which is even superior to that of polycrystalline bulk alloys under the field change of 2 T. Furthermore, it is presented that the reversible Δ T ad can be improved after certain predeformation, which should be attributed to the introduction of certain internal stress by predeformation. Graphical abstract: Unlabelled Image